2023
DOI: 10.3389/fpubh.2023.1003352
|View full text |Cite
|
Sign up to set email alerts
|

Liver injury associated with the severity of COVID-19: A meta-analysis

Abstract: BackgroundThe current 2019 novel coronavirus disease (COVID-19) pandemic is a major threat to global health. It is currently uncertain whether and how liver injury affects the severity of COVID-19. Therefore, we conducted a meta-analysis to determine the association between liver injury and the severity of COVID-19.MethodsA systematic search of the PubMed, Embase, and Cochrane Library databases from inception to August 12, 2022, was performed to analyse the reported liver chemistry data for patients diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Upon literature review, a recent meta-analysis by Yang et al reported that patients with gastrointestinal symptoms had higher AST and ALT than those without the G.I. symptoms, as seen in our case [7] . The most common pattern of liver damage in COVID-19 patients is hepatocellular injury.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Upon literature review, a recent meta-analysis by Yang et al reported that patients with gastrointestinal symptoms had higher AST and ALT than those without the G.I. symptoms, as seen in our case [7] . The most common pattern of liver damage in COVID-19 patients is hepatocellular injury.…”
Section: Discussionsupporting
confidence: 62%
“…One of the commonly reported complications includes acute liver injury with a prevalence of 19 % (range: 1–53 %) [2] , [6] , and the clinical manifestation can range from being asymptomatic to acute liver failure with signs of decompensation [4] . The severity of liver damage usually correlates with the severity of COVID-19 infection [7] , underlying chronic liver disease like alcohol-related liver disease, nonalcoholic fatty liver disease, cirrhosis, autoimmune hepatitis, chronic viral hepatitis, and hepatocellular carcinoma [4] , [8] , [9] , [10] . The underlying pathophysiology of COVID-19-induced liver injury is not clear; however, the proposed mechanism is related to direct cytopathic viral effect, cytokine storm leading to immune-mediated hepatitis, hypoxic injury, drug-induced liver toxicity, and underlying chronic liver diseases [2] , [3] , [7] , [8] as mentioned in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mechanisms may account for the onset and progression of liver damage in COVID-19 [16,[70][71][72]. For example, SARS-CoV-2 RNA and viral particles have been de-Life 2023, 13, 1324 9 of 13 tected in the liver parenchyma of patients with COVID-19 [73][74][75].…”
Section: Discussionmentioning
confidence: 99%